THE RELATIONSHIP BETWEEN THE THEME AND THE CHARACTERIZATION OF THE MAJOR CHARACTER IN OSCAR WILDEâS NOVEL âTHE PICTURE OF DORIAN GRAYâ (1989) - Astuti, Lina Try; Banat, Azizatul (LITERARY CRITICISM, 2014)
This research was focused on descriptive research and analyze the relationship between the theme and the characterization of the major character looked from structuralism theory. The objective of this research is to describe the theme, the characterization of the major character, and the relationship between the theme and the characterization of the major character looked from structuralism theory. Data were collected by literature study such as: literature, books, references related to this research. The results of this research showed that the major theme of this novel is art as a mirror, there are some minor themes as add meaning: good vs. evil (physical and deeds), youth, vanity as original sin, mortality, morality and ethics, and friendship. The major character of the novel is Dorian Gray. The analysis of characterization which is used, is a dramatical characterization. The relationship between the theme and the characterization of the major character is very close. Dramatical characterization shows the characterization of the major character through four questions: What the major character done, What the major character said, How the major character faces problem, and How the other character judge the major character.Keywords: theme, characterization, major character, structuralism theory, Â Â dramatic delineation